Cacth Composition and Fishery Economy of Small-Scale Raft Lift Net in Ohoi Namar, Southeast Mollucas Regency - Picaulima, Simon Marsholl; Ngangun, Tati Atia; Suharyanto, Suharyanto (Agrikan Jurnal Agribisnis Perikanan, 2022)
The composition of the catch that is different every season will have an impact on the fishery economic benefits of small-scale raft lift net. The purpose of this study was to analyze the catch composition and fiheries economic raft lift net business in every season. The research method used in this study is a survey research method, respondent determination techniques based on purposive sampling. The data analysis used is fishing ground analysis, catch composition and fiheries economic. The results showed that the composition of the highest catches in the transitional season 1 was blue scad (Decapterus macarellus) at 43%, in the east season was white anchovy (Stolephorus devisi) at 44%, and transition season 2 was yellow trout (Selaroides leptolepis). by 30%, the highest total revenue in the east season of Rp. 205,657,000, the highest total production cost in the east season of Rp. 133,171,972, the lowest efficiency of Rp. 4,935.70/Kg and the highest effectiveness of 0.000202 Kg/Rp in the transition season 2, the value of productivity IDR 1.54 and a profit of IDR 72,485,028 occurred in the east season.